The acquisition of English grammar among Malay-English bilingual primary school children - Mohamed Salleh, Rabiah Tul Adawiyah; Di Biase, Bruno; Ramlan, Wan Nur Madiha (UKM press, 2020)
Studies to document the English acquisitional trajectory of Malaysian learners are scant and this normative data is imperative for syllabus-designers, policy-makers, teachers as well as linguists to understand the root cause of the students’ low proficiency in English. Hence, this article presents the acquisition of English grammar among Malay-English bilingual primary school children. Seven nine-year-old children, who have attended the same primary school which employed the Standard Based Curriculum for Primary Schools (KSSR) syllabus for 2 years (i.e., since they were 7 years old) became the subject of this study. The speech output of the children was elicited from two communicative tasks. Their English grammatical acquisition was then analysed using the Processability Theory (PT) framework. Other than the school environment, the children’s home language factor was also examined. The results indicate that other than the home language environmental factor, the children’s language aptitude also contributes to their English grammatical acquisition. In terms of PT’s developmental stages, it was also found that the children’s acquisition of English morphology adheres to the stages predicted by PT. The findings also lend credence to PT’s typological applicability across different populations.